Bronchoalveolar lavage chitotriosidase activity as a biomarker of sarcoidosis - Harlander, Matevž; Salobir, Barbara; Zupančič, Mirjana; Terčelj, Marjeta (Sarcoidosis, Vasculitis and Diffuse Lung Diseases, 2016)
Background: Chitotriosidase (CTO) was shown to be a good biomarker of sarcoidosis. Increased levels in bronchoalveolar lavage fluid (BALF) were reported and associated with more severe forms of the disease. Objectives: The aim of the study was to evaluate the value of CTO in BALF as a routine biomarker of sarcoidosis. Methods: The study included 85 patients in 9 control subjects in whom serum and BALF CTO were measured. Results: Significantly higher CTO levels were detected in BALF of sarcoidosis patients than in control subjects (p < 0.001). There was good correlation between serum and BALF CTO levels in sarcoidosis patients (Spearman’s Rho 0.481, p < 0.001). Serum but not BALF CTO had good correlation with clinical parameters. Only in a group of patients with BALF CTO above upper normal range there was association of BALF CTO with impaired FVC (p = 0.020) and chest radiograph score (0-2 vs. 3-4, p = 0.016). Conclusions: In comparison to serum CTO no additional benefit of determining CTO in BAL for routine sarcoidosis workup was shown. (Sarcoidosis Vasc Diffuse Lung Dis 2015; 32: 313-317)